The Effect of Recitation Quran on the Human Emotions - Nayef, Eman Ghanem; Muhammad Nubli, Abdul Wahab (Human Resource Management Academic Research Society (HRMARS), 2018)
This research presents the works related with the human emotional affected by Quran recitation. Recitation of the Holy Quran is governed by a variety of rules called "Tajweed rules". There are many factors that affect the human emotion like heart rate variability and breathing behaviour, internal and external to the human body. Quran recitation produced a significant relaxation which may be due to that Quran has specific effect on human heart which lead to effect some hormone and chemical are responsible for relaxation